WORD OF MOUTH SEBAGAI KONSEKUENSI KEPUASAN PELANGGAN - Eny Purbandari; Dyah Sugandini; Heru Tri Sutiono (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
The objective of this study is to investigate the impact of price and service quality on customer satisfaction to increase words of mouth. Data were collected by distributes questionnaires to 110 patient of Bhayangkara Polda DIY Hospital. Then, data was analyzed using structural equation modeling. The result showed that service quality, price and image have positive effect on patient satisfaction and patient satisfaction has a positive effect on words of mouth. The results also shows that image have the highest effect in creating the satisfaction. Therefore, the models of words of mouth have acceptable.